Leveraging virtual business model innovation: a framework for designing business model development tools. (2nd February 2016) - Ebel, Philipp; Bretschneider, Ulrich; Leimeister, Jan Marco
Abstract: This paper presents a framework for developing tool support for the design and management of new business models. Existing IT tools supporting the process of designing, innovating, and evaluating a company's business model are currently not leveraging the full potential of tool support, because they do not make use of theoretical and empirical knowledge around business model development. Against this backdrop, we analyze existing knowledge on business model design and management, resulting in a first systematization of the activities that are necessary for developing and managing new business models. In order to complement this knowledge and to identify the requirements for supporting these activities, a series of expert interviews is conducted. Based on the results of the interview series, a new business model development tool is created and evaluated. The learnings of this development process are then consolidated in a unified framework. This framework constitutes a new solution for systematically designing tool support for business model development and extends existing literature by highlighting the importance of collaboration between participants in a business model development project. It also provides designers of new business model development tool with an empirically based conceptualization to guide their efforts.